NCLB: Local implementation and impact in southwest Washington state. - Mabry, Linda; Margolis, Linda Mabry; Jason (Education Policy Analysis Archives, 2006)
The research reported here is from the first two years of an ongoing and largely qualitative study to examine the impact of the No Child Left Behind federal education policy on educational practice and climate in elementary schools in two districts in southwest Washington. Based on systematic drop-in observations in classrooms and interviews with teachers and school and district administrators, data indicated that the policy had partially yielded the intended standards-based reforms but at considerable local cost. While most participating administrators described efforts to use NCLB to leverage needed change, most teachers described struggles to sustain best practice and to avoid some negative consequences to their students and schools. Administrators anticipated that resistant teachers would be nudged from the profession, and the greatest attrition among participating teachers was from the fourth-grade level at which the state’s standards-based test was administered. Fourth-grade teachers particularly expressed concern about test-related stress and test-driven curricula interfering with children’s individual needs and with their own ability to provide developmentally appropriate instruction adapted for their particular students. The validity and utility of test results was a local issue.